Dual regulation of the ugp operon by phosphate and carbon starvation at two interspaced promoters. - Kasahara, M (1991)
The ugp operon of Escherichia coli includes genes involved in the uptake of sn-glycerol-3-phosphate and glycerophosphoryl diesters and belongs to the pho regulon which is induced by phosphate limitation. This operon has two transcriptional initiation sites, as determined by S1 nuclease mapping of the in vivo transcripts. The downstream promoter has multiple copies of the pho box, the consensus sequence shared by the pho promoters; the upstream promoter has a consensus sequence for the promoters regulated by cyclic AMP and its receptor protein, CRP. PhoB protein, which is the transcriptional activator for the pho regulon, protected the regulatory region with the pho boxes in DNase I footprinting experiments and activated transcription from the downstream promoter in vitro. Studies with transcriptional fusions between ugp and a promoterless gene for chloramphenicol acetyltransferase show that the upstream promoter is induced by carbon starvation in a manner that required the cya and crp genes. PhoB protein may act as a repressor for this upstream promoter, which also overlaps the upstream third pho box. The downstream promoter was induced by phosphate starvation and requires the PhoB protein for its activation as do the other pho regulon promoters. These results suggest that the two promoters function alternately in responding to phosphate or carbon starvation, thus providing the cell with a means to adapt to these physiological stresses.